Effects of two boron containing compounds and melatonin in a(1-42) toxicity - Ozansoy, Mehmet; Altıntaş, Mehmet Özgen; Kılıç, Ulkan (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY
WOS: 000445952400017
Keywords: Containing; Compounds; Melatonin